Análise de frequência da oscilação postural durante a manipulação dos sistemas somatossensorial, vestibular e visual - Soares, Juliana Corrêa (2022)
The maintenance of postural balance occurs through the performance of the postural control system and any impairment of this system can give rise to body imbalance. Frequency analysis has been widely used in the assessment of postural control. The aim of the study was to evaluate postural sway during manipulation of sensory systems in healthy individuals, comparing the sexes and postural sway in relation to the time of collection. This is an experimental cross-sectional study. The sample consisted of 48 individuals, 23 males and 25 females, with a mean age of 32.21±10.48 years and a BMI of 22.07±3.05 kg/m², exposed to four tests of Sensory Organization (TOS): eyes open, eyes closed, stable and unstable surface, on a force platform. Three trials of 60 seconds were performed, with a one-minute rest interval between them. Acquisition frequency of 100 Hz and data filtered by a 2nd order Butterworth digital filter, adjusted frequency of 20 Hz, and processed through a Matlab routine. The variables used were the displacement amplitude and the medians of the frequencies present in the center of pressure (COP) signals in the anteroposterior and mediolateral directions. For the comparison between the four test conditions, ANOVA of repeated measures and Bonferroni's post hoc was used. For the comparison between the sexes and the comparison between the times (0 - 15s; 16 - 30s; 31 - 50s) during the four test conditions a two-way ANOVA was used. 5% significance level. All analyzes were performed using SPSS version 20.0. The displacement variables and the COP oscillation frequencies were influenced by the manipulation of the sensory systems. The change from stable to unstable surface generated an increase in the frequency of oscillation to maintain postural control (p<0.01). However, there were no significant differences in supplying the visual system when subjects were on a fixed surface, but this suppression altered the frequency of COP oscillation when subjects were on an unstable surface (with cushion). Regarding the comparison between the sexes, the postural control responses were similar, not indicating that sex exerts an influence on these variables. Regarding the collection time, as the collection took place, within each test condition, the individuals showed a decrease in the frequency of oscillation and an increase in the amplitude of displacement of the COP. Adult individuals of both sexes maintain the dynamics of postural control even in visual suppression. During clinical practice or in the rehabilitation phases, more challenging situations should be considered for the maintenance of postural control, since these adults do not have a significant dependence on vision. of oscillation and an increase in the amplitude of displacement of the COP.